Successful treatment with a combination of bee venom immunotherapy and omalizumab for recurrent anaphylaxis after honey bee sting - P C Kathuria; Manisha Rai; Ghulam Hassan (Indian Journal of Allergy Asthma and Immunology, 2021)
Hymenoptera venom hypersensitivity reaction affects about 3% of the general population and a higher percentage (14%–43%) in beekeepers. Bee venom immunotherapy (bVIT) is effective in reducing subsequent severe systemic reactions and has a significant beneficial effect on disease-specific quality of life in both children and adults. In patients with a history of recurrent systemic anaphylactic reaction with bee venom, successful bVIT is difficult to achieve and can often lead to withdrawal of treatment. The combination of bVIT and omalizumab is a good option for these patients. Omalizumab is a humanized nonanaphylactogenic monoclonal anti-immunoglobulin (Ig) E antibody against the Cε3 domain of IgE to reduce the allergenicity, if combined with bVIT. We describe a successful treatment with combined omalizumab and bVIT in a case of recurrent anaphylaxis by honey bee sting hypersensitivity. Herein, subcutaneous omalizumab 150 mg was started 15 days before the initiation of bVIT and subsequently once a month for 30 months along with cluster doses of bVIT till the cumulative dose of 100 μg was achieved successfully.